Kingdom of the Netherlands-Netherlands Antilles : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix explores four policy issues-fiscal policy, public sector pension reforms, monetary management, and labor market performance-which are crucial for understanding the recent performance of the economy of the Netherlands Antilles and which will need to be addressed to restore the prospect of durable economic growth. The paper reviews experience with fiscal adjustment in the Netherlands Antilles, focusing in particular on the 1996-97 adjustment program. The paper also analyzes the sustainability of the public pension system of the country.